Rehabilitasi Medik Terhadap Pasien yang Menggunakan Ganja Medis dalam Pengawasan Sebagai Pemenuhan Hak Atas Kesehatan di Indonesia - Ismansyah Ismansyah; Siska Elvandari; Syofirman Sofyan (UNES Law Review, 2023)
The pattern of medical rehabilitation carried out by countries that legalize the use of medical marijuana, and the process of healing users from narcotic dependence varies, so various strategies and therapies for marijuana use are needed in various countries with emphasis on several indicators, such as: religion, form, and/or the basis of a country, what legal system is adopted by a country, what institutions exist in a country, which really focuses on the values ​​that live and grow in that country, which are feared will affect the aspects of national and state life , undermines the stability of the nation's economy, which of course affects a country's efforts to realize the welfare elements of a country, one of which can be obtained through legal development in general, as well as health development in particular.